Hodgkin disease: Hodgkin and Reed-Sternberg cells picked from histological sections show clonal immunoglobulin gene rearrangements and appear to be derived from B cells at various stages of development. - Küppers, R (1994)
Hodgkin disease (HD) is characterized by a small number of putative malignant cells [Hodgkin and Reed-Sternberg (HRS) cells] among a background of lymphocytes and histiocytes. The lineage of HRS cells is still elusive and a clonal origin of these rare cells has not formally been demonstrated. We isolated HRS cells by micromanipulation from histological sections of three cases of Hodgkin lymphoma (each representing a distinct subtype of the disease) and analyzed individual cells for immunoglobulin variable (V) gene rearrangements by PCR. In each of the three cases a single heavy-chain V (VH) (and in one case, in addition, a kappa light-chain) gene rearrangement was amplified from the HRS cells, identifying these cells as members of a single clone. A potentially functional VH rearrangement was obtained from a case of nodular sclerosis HD. Somatic mutations and intraclonal diversity in the VH genes indicate a germinal center B-cell origin of the HRS cells in a case of lymphocyte-predominant HD, whereas in a case of mixed-cellularity HD the sequence analysis revealed only nonfunctional V gene rearrangements, suggesting a pre-B-cell origin. This indicates that HRS cells can originate from B-lineage cells at various stages of development.